A case study of the significance of family values in the use of residential space - Miranda, Patricia D.
This case study sought to examine how a nuclear Filipino family living in a university housing unit utilized available space to address their needs. It also aimed to determine how Filipino values influenced the use of space. Methods employed in the study include participant-observation, interview, survey, and photo and space-documentation. The subject was a nuclear family composed of a father, mother, and four sons living in a two-storey row house. The instruments of the study included a questionnaire, journal, recorder, camera and metric tape. Results showed that the family had more individual than group activities. The individual activities were diverse and some were performed simultaneously with group activities in the living room. The space plan and design of the house did not correspond to the lifestyle of its current occupants so necessary adjustments were applied in the use of space. This resulted to multi-functional and under-utilized areas/rooms in the house. Most of the complaints on the areas were design-related concerns. Cultural values played a significant role in the use of space. It intervened to resolve conflicts or prioritize activities in the space. The manner of executing some individual activities also reflected some cultural values most dominant of which are pakikisama and group-centeredness. Cultural values can be identified in the physical aspect of the space but some can also manifest in the use of space.